Perbedaan Tingkat Stres Pada Ibu Rumah Tangga yang Menggunakan dan Tidak Menggunakan Pembantu Rumah Tangga - Putri, Ketut Ariyani Kartika; Sudhana, Hilda (Jurnal Psikologi Udayana, 2013)
Household chores is a non formal complex task and its not an easy thing to do. To finish the house work needs a lot of time and energy, also most of it must be done in the house every day, especially if no one help to finish it. It creates an isolated condition and may potentially cause stress. Some housewives prefer to hire a housekeeper to help to complete house works daily. This study is aiming to see the difference level of stress between housewives who use and does not use a housekeeper.   Subjects in this research are 180 housewives aged between 30-55 years old who are not working and lives in the Denpasar area. Sampling technique in this study are incidental sampling. The scale used is the scale of the stress on housewives. From the 54 available items, 28 items declared valid with reliability values  0, 901 and 26 items fall. Method of analyzing data used in this research is the analysis of non parametric Two Independent Sampel. Results from test data analysis is that there is a significant value of p= 0.000 which indicates a significant difference between both group of housewives, so that the conclusions in this research is that there are significant difference levels of stress in housewives who use and does not use a housekeeper. Thus the alternative hypothesis (Ha) in this study is accepted.   Keywords : Housewives, housekeeper, stress.